2022
DOI: 10.1038/s41598-022-07018-5
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific interspecies interactions between co-isolated pairs of Staphylococcus aureus and Pseudomonas aeruginosa from patients with tracheobronchitis or bronchial colonization

Abstract: Dual species interactions in co-isolated pairs of Staphylococcus aureus and Pseudomonas aeruginosa from patients with tracheobronchitis or bronchial colonization were examined. The genetic and phenotypic diversity between the isolates was high making the interactions detected strain-specific. Despite this, and the clinical origin of the strains, some interactions were common between some co-isolated pairs. For most pairs, P. aeruginosa exoproducts affected biofilm formation and reduced growth in vitro in its S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…In terms of inhibitory effects against gram-positive bacteria, P. aeruginosa strain ATCC27853 showed notable activity, exhibiting strong inhibition against S. aureus ATCC29213 and B. cereus ATCC14579 after 48 h of incubation. However, it showed no inhibition against S. aureus ATCC29213 and B. cereus ATCC14579 after 24 h. Similar studies have reported the varying inhibitory effects of P. aeruginosa strains against different gram-positive bacteria, highlighting the strain-specific nature of these effects [33][34][35].…”
Section: Discussionsupporting
confidence: 63%
“…In terms of inhibitory effects against gram-positive bacteria, P. aeruginosa strain ATCC27853 showed notable activity, exhibiting strong inhibition against S. aureus ATCC29213 and B. cereus ATCC14579 after 48 h of incubation. However, it showed no inhibition against S. aureus ATCC29213 and B. cereus ATCC14579 after 24 h. Similar studies have reported the varying inhibitory effects of P. aeruginosa strains against different gram-positive bacteria, highlighting the strain-specific nature of these effects [33][34][35].…”
Section: Discussionsupporting
confidence: 63%
“…The strain-specific nature of synergy in mixed-species biofilms on the one hand emphasizes the significance of strains, rather than species, in studying bacterial interactions and on the one hand, it has implications for the development of synthetic bacterial communities. The role of inter-strain phenotypic diversity in modulating interactions in mixed species biofilms has been reported, mainly in dual-species biofilm settings ( Gomes-Fernandes et al, 2022 ). L. monocytogenes strains of food origin have been reported to show large variations in competitive growth in different mixed-species biofilm settings ( Heir et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus) during interspecies competition and establishment of the pathogen in its niche [49]. A co-isolated pair of S. aureus and P. aeruginosa from patients with tracheobronchitis or bronchial colonization revealed that P. aeruginosa exoproducts impacted biofilm formation and decreased in vitro growth of its S. aureus counterpart, while S. aureus did not impair biofilm formation and triggered swarming motility in P. aeruginosa [50].…”
Section: Identification Of New Potential Therapeutic Targets Against ...mentioning
confidence: 99%